The Existence of Customary Law Communities and Citizenship Rights: Implementation of Sociological Laws and Customs in Aceh in the era of Globalization - Sasono, Satryo; Isharyanto, Isharyanto (HUKUM PEMBANGUNAN EKONOMI, 2023)
Aceh is a province located at the western tip of Indonesia, namely Sumatra Island. Aceh was given special autonomy authority in running the government and self-regulating the local community’s interests by the laws and regulations in the system and the Unitary State of the Republic of Indonesia based on the 1945 Constitution of the Republic of Indonesia. The existence of geographical differences and patterns of interaction caused the tribes in Aceh different. This privilege is related to regulations concerning the fields of religion, custom, education, and clergy as stipulated in Law no. 44 of 1999. This research discusses one of Aceh's customary laws, namely qonun and jinayat, and how Aceh's history was formed up to the challenges that will be faced by the people of Aceh in the era of globalization. The purpose of this research is to explore and find out more about the diversity of tribes in Aceh and find out how the tribes in Aceh maintain their customary law from the shocks of social change in the development of the globalization era.